Quantitative MRI Helps to Detect Hip Ischemia: Preclinical Model of Legg-Calvé-Perthes Disease - Johnson, Casey P. (Radiology, 2018)
PURPOSE: To determine whether quantitative MRI relaxation time mapping techniques can help to detect ischemic injury to the developing femoral head. MATERIALS AND METHODS: For this prospective animal study conducted from November 2015 to February 2018, 10 male 6-week-old piglets underwent an operation to induce complete right femoral head ischemia. Animals were humanely killed at 48 hours (n = 2) or 4 weeks (n = 8) after the operation, and the operated and contralateral-control femoral heads were harvested and frozen. Thawed specimens were imaged at 9.4-T MRI by using T1, T2, T1 in the rotating frame (T1ρ), adiabatic T1ρ, relaxation along a fictitious field (RAFF), and T2* mapping and evaluated with histologic analysis. Paired relaxation time differences between the operated and control femoral heads were measured in the secondary ossification center (SOC), epiphyseal cartilage, articular cartilage, and metaphysis and were analyzed by using a paired t test. RESULTS: In the SOC, T1ρ and RAFF had the greatest percent increases in the operated versus control femoral heads at both 48 hours (112% and 72%, respectively) and 4 weeks (74% and 70%, respectively). In the epiphyseal and articular cartilage, T2, T1ρ, and RAFF were similarly increased at both points (range, 24%–49%). At 4 weeks, T2, T1ρ, adiabatic T1ρ, and RAFF were increased in the SOC (P = .004, .018, < .001, and .001, respectively), epiphyseal cartilage (P = .009, .008, .011, and .007, respectively), and articular cartilage (P = .005, .016, .033, and .018, respectively). Histologic assessment identified necrosis in SOC and deep layer of the epiphyseal cartilage at both points. CONCLUSION: T2, T1 in the rotating frame, adiabatic T1 in the rotating frame, and relaxation along a fictitious field maps are sensitive in helping to detect ischemic injury to the developing femoral head. © RSNA, 2018 Online supplemental material is available for this article.